Analysis and prediction of micro injection molding part using moldflow simulation software - Mohammad Farhan, Othman (2012)
The demands of micro injection molding parts has been increase tremendously that promote the potential of its huge markets in this new millennium. The complexity of producing micro injection molding parts is much higher compare to typical injection molding process. Normally, micro injection molding parts was produce by using specially built micro injection molding machine or modified conventional injection molding machine that suit the process of producing micro parts. However, micro injection molding parts can also be ejected in conventional injection molding process. The problem is the amount of plastic material wasted from the feed system design is always more than 90%. This is due because the size of conventional injection molding process biggest than micro injection molding process. But nowadays, that problem can be predicted earlier by using Moldflow simulation software analysis. Moldflow simulation software can be used to determine the best feed system design, predict possible molding defects and suggest optimum injection molding parameters. This project was conducted analyze and predict of micro injection molding part using Moldflow simulation software. The analysis is made for three different size of runner that is 4mm, 5mm and 6mm. For the melt temperature material at 230°C and mould at both sides is 50°C. The Moldflow results are barely different. From the result, we can determine the best of runner before fabrication process take place. This analysis may reduce miscellaneous cost. The comparison need to be undertaken. The analysis can tell the best fill time, injection pressure, shot weight, air traps, weld line, time to freeze, temperature at flow front, and etc. The analysis will determine that weather Moldflow is suitable for micro plastics or not.